Peranan Koperasi Simpan Pinjam Pembiayaan Syariah (KSPPS) Dalam Meningkatkan Usaha Mikro Kecil dan Menengah Masyarakat - Bakti Toni Endaryono; Lukman Ar Rasyid; Yanti Hasbian Setiawati (Reslaj : Religion Education Social Laa Roiba Journal, 2019)
This study aims to determine the role of BMT Binaul Ummah erformance in improving smallbusinesses in Bogor Selatan Sub-District, Bogor City and to find out the results of the BMT Bianul Ummahfor small businesses in Bogor Selatan Sub-District, Bogor City. Triangulation method used in this study isdata triangulation. In triangulating data, researchers use several data sources to collect data with thesame problem, meaning that the data in the field is taken from several different sources of research objects.In collecting data, researchers use different techniques or methods, namely comparing the results ofinterviews with the data sources of researchers’ observations and the contents of related documents, theresults of research instrument trials show good instrument reliability. Conclusion of research results Theexistence of BMT Binaul Ummah has a role and benefits in helping improve micro small and mediumbusinesses in the vicinity, namely by collecting ZIS funds (Zakat, Infaq, and Shodaqoh) from the communityand then distributed to those entitled to receive it in the context of poverty alleviation efforts . In addition,the existence of BMT Binaul Ummah is able to minimize the space for the role of loan sharks whose existenceis very detrimental to small businesses. And also BMT provides capital to applicants for funds that areconsidered productive so as to be able to increase micro small and medium enterprises.Keywords: Role of BMT Cooperatives, Micro Small Business